TUMBUHKAN SEMANGAT WIRAUSAHA PADA SISWA MA GHAYATUL ANWAR MELALUI PEMANFAATAN TEKNOLOGI DI ERA BISNIS DIGITAL - Moh. Baqir Ainun; Nur Qoudri Wijaya; Liyanto Liyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Universitas Abdurachman Saleh Situbondo, 2025)
Increasing awareness of the younger generation to utilize technology and the internet in accordance with current and future business developments and opportunities is an important thing to do. It becomes a problem for the nation and region when not all high school graduates can continue their studies to college and find work after graduating from high school, because it will increase the unemployment rate. One way to reduce the unemployment rate of high school graduates is to encourage high school graduates to want to become entrepreneurs. However, students who have graduated from high school find it difficult to start a business because of their lack of entrepreneurial knowledge. This phenomenon occurs in MA Ghayatul Anwar students. The knowledge of MA Ghayatul Anwar students in utilizing digital technology for entrepreneurship is very low, so that it has an impact on the interest in becoming entrepreneurs which is also low. Therefore, this PkM activity is carried out to increase the knowledge of partners in utilizing digital technology in entrepreneurship, as well as to increase the interest of partners in becoming entrepreneurs by utilizing digital technology. The methods used are socialization and training carried out to overcome the problems faced by partners. Based on the results of the pre-test, socialization, and post-test that have been carried out, it can be concluded that the knowledge of partners in utilizing digital technology for entrepreneurship has increased. In addition, the interest of partners in becoming entrepreneurs by utilizing digital technology has also increased.